Platelet counts affect the association between hyperhomocysteinemia and pregnancy complications - Bin Yu; Bin Zhang; Xiaoya Han; Wei Long; Wenbo Zhou; Xiaosong Yuan (BMC, 2023)
Abstract Background The joint effect of platelet and other modifiers on the risk of pregnancy complications is unknown. This study investigated whether platelet count (PC) and total homocysteine (tHcy) level have a synergistic effect on the incidence of pregnancy complications in a Chinese population. Methods Total 11,553 consecutive pregnant women who received whole blood cell and biochemical tests at the time of admission for labor in Changzhou Maternal and Child Health Care Hospital were analyzed. The primary outcome was the prevalence of pregnancy complications: gestational diabetes mellitus (GDM), intrahepatic cholestasis of pregnancy (ICP), pre-eclampsia (PE), and pregnancy induced hypertension (PIH). Results The prevalence of GDM, ICP, PE, and PIH was 8.4%, 6.2%, 3.4%, and 2.1%, respectively. The highest rate of ICP (28.6%) was observed in women with high tHcy (> 15 μmol/L) and low PC (quartile 1); and the lowest rate of GDM (0.6%) was found in women with high tHcy and high PC (quartiles 2 to 4). In low PC group, the prevalence of ICP in women with high tHcy was significantly higher than that in women with low tHcy (≤ 15 μmol/L) (28.6% vs. 8.4%), representing an absolute risk increment of 20.2% and a relative risk increment of 3.3-fold (OR: 3.34; 95% CI: 1.55, 7.17; P = 0.002), whereas no joint effect was observed among high PC group. Conclusions Among Chinese pregnant women, one subgroup (high tHcy and low PC) has the highest risk of ICP and another (high tHcy and high PC) has the lowest risk of GDM; tHcy and platelet could be used as indicators to identify the women with high risk of ICP or low risk of GDM.